Development of Early Detection Instruments for Development in Children with Special Needs - Nurwening Tyas Wisnu; Tutiek Herlina; Tinuk Esti Handayani (Journal of Global Pharma Technology, 2020)
Golden age is a very important period to pay attention to the development of children, especially if there is a suspicion that the growth and development is different from children of his age. Objective: To develop early detection instruments for growth and development in children with special needs. Method: The research design was Research and Development carried out in 2 stages. The first stage was identifying the DDTK instrument from the SDIDTK and Denver II manuals and then conducting FGDs with 70 participants. The second stage is test results development of 30 parents and their children with special needs to get recommendations on the results of instrument development. Methods to identify children with special needs by means of observation, interviews, documentation, orders and a combination of 3 methods. Data analysis using descriptive analysis, validity test and using product moment and reliability using Alfa Chronicle. There are eight questionnaires to detect blind, deaf, mentally retarded, disabled, disabled, autistic, ADHD and special intelligent. The development of this instrument has the addition of aspects of behavior and physical appearance that exist in children. The development of instruments for early detection of development of children with special needs consists of 8 questionnaires. The results of the instrument trial showed good results and the opinion of special school teachers and ABK therapists was very positive with the development of this instrument so it is recommended to be disseminated to posyandu cadres, the community and health workers. Keywords: instrument, early detection of growth and development, children with special needs